Dental Health Education Promotion using Video Blogs (Vlog) and Treatment Methods on Teething Practices in Basic School Children in Bandung City - Irwan Supriyanto; Gilang Yubiliyana; Insi Farisa Desy Arya (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
One of the ways to overcome dental and oral health problems is by brushing teeth, the optimal result of brushing teeth properly is the morning after breakfast and the night before going to bed. Tooth brushing using toothbrushes is a form of dental plaque removal and prevention of accumulation of the teeth and gingival surface because plaque is the main etiological factor of periodontal disease and is associated with dental caries, therefore in removing plaque it is very important to determine long-term success in preventing caries tooth. Through the promotion of dental health education, it is expected to increase knowledge and foster awareness of the importance of toothbrushes to maintain healthy teeth and mouth. The purpose of this study is to recognize the differences in the influence of dental health education promotion using blog videos (vlog) with lecture methods on the practice of brushing teeth. This type of research is a Quasi-experiment with the design of the Two-Group Design. Samples were taken by purposive sampling namely SD Panghegar and SD Sukarela. Univariate and bivariate analysis with Wilcoxon and Mann-Whitney tests. This study shows the promotion of dental health education using vlog and lectures has an effect on increasing the practice of brushing teeth. It can be seen that there is an increase in the practice of brushing teeth from the value of pre-test and post-test respectively with a value of p 0.05. But based on statistical tests there is no significant difference in influence by using both methods with a value of p = 0.035. This means that both methods are effective in increasing knowledge about the practice of brushing teeth, and there is no significant difference between the promotion of dental health education using vlogs and using lectures.